Modified Class-F power amplifier design with fundamental frequency output impedance load - Pakasiri, Chatrpol; Manasummakij, Prateep; Wang, Sen (My University, 2021)
A modified Class-F power amplifier with medium output power at 433 MHz was designed, simulated and implemented in this paper. The design process used a load condition of 1) output impedance of the amplifier at the fundamental frequency, 2) short-circuit loads at the even harmonics and 3) open-circuit loads at the odd harmonics. By biasing the circuit to be a typical Class-F, the circuit yielded moderate efficiency as the load condition was different from the optimum one. By strongly biasing the circuit toward that of Class-A, the load condition approached the optimum, but the circuit still yielded moderate efficiency due to the low efficiency nature of a Class-A amplifier. By proper choice of the operating point in Class-AB, a prototype circuit, with 9 dBm input power, yielded a maximum PAE of 68.5% with output power 21.8 dBm. Furthermore, at 11 dBm input power, the prototype yielded a better PAE 79.6% with 23.2 dBm output power. Our design procedure did not need expensive load-pull equipment.
Keywords: Class-F power amplifier; Operating point; UHF power amplifiers